Design and synthesis of novel dihydropyridine- and benzylideneimine-based tyrosinase inhibitors - Ahmad, Ifraz; Parveen, Warda; Noor, Shah; Udin, Zahoor; Ali, Amjad; Ali, Ijaz; Ullah, Riaz; Ali, Hamid (Frontiers in Pharmacology, 2024)
Tyrosinase (TYR) inhibitors are very significant as they inhibit enzyme tyrosinase activity, and its inhibition is vital for skin care, anticancer medication, and antibrowning of fruits and vegetables. This work presents a novel and economical route for the preparation of new synthetic tyrosinase inhibitors using amlodipine (4). The novel conjugates 6 (a–o) were designed, synthesized, and characterized by spectroscopic analyses, including Fourier transform infrared and low- and high-resolution mass spectroscopy. The purified compound 4 was refluxed with various aldehydes and ketones 5 (a–o) for 5–8 h in methanol at 60°C–90°C. This research modified the drug in a step-by-step manner to develop therapeutic properties as a tyrosinase inhibitor. The structures of synthesized ligands 6 (a–o) were established based on spectral and analytical data. The synthesized compounds 6 (a–o) were screened against tyrosinase enzyme. Kojic acid was taken as standard. All the prepared compounds 6 (a–o) have good inhibition potential against the enzyme tyrosinase. Compounds 6o, 6b, 6f, and 6k depicted excellent antityrosinase activity. Compound 6k, with an IC50 value of 5.34 ± 0.58 µM, is as potent as the standard kojic acid (IC50 6.04 ± 0.11 µM), standing out among all synthesized compounds 6 (a–o). The in silico studies of the conjugates 6 (a–o) were evaluated via PatchDock. Compound 6k showed a binding affinity score of 8,999 and an atomic contact energy (ACE) value of −219.66 kcal/mol. The structure–activity relationship illustrated that the presence of dihydropyridine nuclei and some activating groups at the ortho and para positions of the benzylideneimine moiety is the main factor for good tyrosinase activity. The compound 6k could be used as a lead compound for drug modification as a tyrosinase inhibitor for skin care, anticancer medication, and antibrowning for fruits and vegetables.